2007
DOI: 10.1080/15216540601188546
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric effects on oxidative and nitrosative reactions of cell‐free hemoglobins

Abstract: SummaryA review of the oxidative and nitrosative reactions of cell-free hemoglobin-based oxygen carriers (HBOCs) shows that these reactions are intimately linked and are subject to allosteric control. Cross-linking reactions used to produce HBOCs introduce conformational constraints and result in Hbs with reduced responses to heterotropic and homotropic allosteric effectors. The Nernst plots of heme oxidation of cross-linked HBOCs are shifted to higher potentials relative to unmodified Hb in the absence of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…In both Hb and Mb these two properties are intrinsically coupled: as ligand affinity (P 50 ) increases due to conversion to R-state, the heme redox potential (E1 ⁄ 2 ) decreases. Recently, the half-life of the reaction of nitrite with HbA and modified hemoglobins developed as potential blood substitutes was shown to decrease (so the reaction gets faster) as the redox potential increased (31). Based on these data the authors concluded that ligand affinity, rather than redox potential, is the major determinant of the nitrite/Hb rate in these samples.…”
mentioning
confidence: 77%
“…In both Hb and Mb these two properties are intrinsically coupled: as ligand affinity (P 50 ) increases due to conversion to R-state, the heme redox potential (E1 ⁄ 2 ) decreases. Recently, the half-life of the reaction of nitrite with HbA and modified hemoglobins developed as potential blood substitutes was shown to decrease (so the reaction gets faster) as the redox potential increased (31). Based on these data the authors concluded that ligand affinity, rather than redox potential, is the major determinant of the nitrite/Hb rate in these samples.…”
mentioning
confidence: 77%
“…The results in Table 1 also show that inorganic anions and inositol hexaphosphate (IHP), effectors that lower Hb's O 2 affinity, exert opposite effects on the rate of nitrite-induced oxidation. These results show that the conformation and reactivity of Hb in its physiologically important redox reactions can be variably affected by the allosteric effects of anions, and by constraints induced by cross-linking reactions (18).…”
Section: Redox Reactions Of Hb With Nitritementioning
confidence: 92%
“…The reduction occurs at different rates for varied forms of HBOCs. Notably, when the oxidized forms of Bis(3, 5-dibromosalicyl)fumarate (DBBF)-Hb and a bovine polymerized Hb (OxyglobinÔ) were rapidly mixed with ascorbate, reduction of ferryl Hb back to ferric by ascorbate was found to be significantly faster for Oxyglobin (t 1/2 = 0.018 s) than for DBBF (t 1/2 = 0.13 s) (18). These findings offer important implications for clinical therapies for conditions where cell-free Hbs are present at abnormally high levels, or for improved conditions for injection of HBOCs.…”
Section: Effects Of Free Radical Scavengers On the Hb-induced Oxidatimentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the half-life of the reaction of nitrite with deoxyhemoglobin and modified hemoglobins developed as potential blood substitutes was shown to decrease (reaction getting faster) as the redox potential increased. 27 Based on these data, the authors concluded that ligand affinity, rather than redox potential, is the major determinant of the nitrite-deoxyhemoglobin reaction rate in these samples. In another study, the rate that deoxygenated normal adult hemoglobin, HbA 0 , reacts with nitrite was compared with the rate that sickle cell hemoglobin, HbS, reacts with nitrite.…”
Section: Redox Potential and Ligand Accessibilitymentioning
confidence: 99%